Translation of the Adapted Version of the Ecuadorian Literature Work “Cumanda” for the Development of EFL Reading Comprehension Skills at A2-B1 for 6th Grade Students. - Barrera Perlaza, Mikeya Katherine (2024)
This work focuses on the design and development of culture-bound reading material out of the translation of the adapted version of the literature work “Cumanda” by Juan Leon Mera. The target audience are 6th grade students with an A2-B1 level of English in the EFL classrooms. The project incorporates cultural relevance into language instruction by using literature that represents the students’ heritage. The main goal was to contribute to higher levels of students’ engagement, comprehension and critical thinking through their exposure to culture-bound reading material with post reading activities that were developed around the translated version of “Cumanda”. The results of the survey applied show that the incorporation of “Cumanda” could considerably improve students’ motivation and reading comprehension skills by exposure to contextually relevant material. The adaptation of the text to suit students’ language proficiency facilitates better understanding and retention of concepts. Furthermore, the activities encourage the development of critical thinking by allowing students to express their reflections on the story. The study recommends continued use of adapted literary works to support language learning in culturally meaningful ways.